Pentingnya Pelaksanaan Pelatihan On The Job Training Dengan Methode Choaching Untuk Meningkatkan Kinerja Karyawan ( Studi Kasus Pada Restoran A&W Store Mall Of Serang ) - Ahyakudin Ahyakudin (FEB Universitas Sultan Ageng Tirtayasa, 2017)
The dynamics of the environment that always turned demanding company to obtain the quality of human resources .training and development is common frequently done by the company ,because placement employees directly in a job is not guarantee they’ll succeed . New employees often feel not sure about the role of and their responsibility . So it can be assumed that training and development is very important for the workforce to work more mastered and better for the work being served Restaurant A & W has its own management function in each of its branches led by a Manager in charge of Supervisors and other divisions such as Kitchen, Cashier, Preparation and Waiter and waitress. In this industry, A & W not only sells food and beverage products, but also in terms of service / service that can satisfy consumers. To get quality service required Human Resources quality as well. Formula How the training process in A & W Restaurant store Mall of Serang, How the training method applied in A & W Restaurant store Mall of Serang, How many participants, objectives and how the evaluation process Training at A & W Restaurant store Mall of Serang. Training methods On-the-job training, Design of Training Programs. conclusion in this research is employee training method at A & W restaurant store MOS Serang is on the job training that is practice work while practicing with technique Coaching in this case supervisor who become trainer to guide new employees to work in accordance with the task and its function which has been set based on standardization company.